Pablo Picasso Na Kongresie Intelektualistów - PAP (NC, 2026)
Pablo Picasso (on the left) at the World Congress of Intellectuals in Defense of Peace
Droits : Licence indiquee par Wikimedia Commons
Keywords: peinture; peintres; artistes peintres; picasso; photo; archives photographiques; photographie; Art